2017
DOI: 10.3389/fenvs.2017.00087
|View full text |Cite
|
Sign up to set email alerts
|

Rationally Managed Pastures Stock More Carbon than No-Tillage Fields

Abstract: A significant share of Greenhouse Gases (GHG) produced from agriculture comes from cattle farming. The reduction in GHG emissions from ruminants fed with grains has led some researchers to recommend such a diet as a means of mitigating emissions in the sector. A more accurate balance of emissions, however, must include the carbon (C) stocked by feed crops. Within the grain production system, no-tillage (NT) cultivation systems have a greater capacity to increase and store soil organic carbon (SOC). Within graz… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
15
0
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(19 citation statements)
references
References 41 publications
0
15
0
2
Order By: Relevance
“…Pasture management is the gold standard for increasing the sustainability of grazing systems. While we showed the best RP to reduce the CH 4 emission from cattle, other studies have shown that plants from well-managed pastures also have the ability to sequester C from the atmosphere during photosynthesis (Seó et al, 2017;Stanley et al, 2018). When the amount of C emitted is lower than the amount that is being accumulated in soil by plant roots, we have a positive balance of C, and the livestock emissions are indeed offset (Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Pasture management is the gold standard for increasing the sustainability of grazing systems. While we showed the best RP to reduce the CH 4 emission from cattle, other studies have shown that plants from well-managed pastures also have the ability to sequester C from the atmosphere during photosynthesis (Seó et al, 2017;Stanley et al, 2018). When the amount of C emitted is lower than the amount that is being accumulated in soil by plant roots, we have a positive balance of C, and the livestock emissions are indeed offset (Silva et al, 2016).…”
Section: Discussionmentioning
confidence: 57%
“…In practice, VRG enables high nutritional value and productive pasture towards improving animal performance, including the reduction of environmental impacts like enteric CH 4 emissions (Stanley et al, 2018). Moreover, VRG pastures are associated with high soil carbon (C) accumulation due to the increase biocenosis that increase and conserve the soil organic matter (Seó et al, 2017) that helps reduce carbon dioxide (CO 2 ) concentration in the atmosphere and further mitigate GHG emissions (Stanley et al, 2018). Moreover, this system can reduce overgrazing, which potentially protects the soil against erosion and degradation.…”
Section: Introductionmentioning
confidence: 99%
“…Additionally, improving field fertilizer and manure application strategies such as urea (here on corn fields) in conjunction with urease inhibiters could significantly decrease N losses and N 2 O emission from soils [72]. The reduction in GHG emissions from ruminants fed with grains is therefore just one part of the picture, as a more accurate accounting of emissions and milk production must include the C sequestered by feed crops [73]. Here, pastures had greater carbon uptake, highlighting the need to include farm practices in development of GHG budgets [73].…”
Section: Seasonal Ghg Budgets and Recommendations For Reducing Ghg Emmentioning
confidence: 99%
“…The reduction in GHG emissions from ruminants fed with grains is therefore just one part of the picture, as a more accurate accounting of emissions and milk production must include the C sequestered by feed crops [73]. Here, pastures had greater carbon uptake, highlighting the need to include farm practices in development of GHG budgets [73].…”
Section: Seasonal Ghg Budgets and Recommendations For Reducing Ghg Emmentioning
confidence: 99%
See 1 more Smart Citation